Interviews on student perspectives of agricultural feminism at Kansas State University - Denchfield, Ashleigh Diane (Kansas State University, 2023)
The goal of this research is to understand student perceptions of agricultural feminism in the College of Agriculture at Kansas State University. This research will reveal insights into the state of students' education concerning disenfranchised groups in agriculture and may provide future recommendations for agricultural education at Kansas State University. Current research in the College of Agriculture at K-State says that agricultural students are open to diversity. The objective of this research is to understand student perceptions of agricultural feminism at Kansas State University and infer insights to improve the current state of agricultural education. In this thesis, my main inquiry is that if students are open to diversity, will they want to express their perspectives of agricultural feminism the gender gap, mentoring, and intersectionality in agriculture? I am interested in learning how farmer identity is perceived within different sects of agriculture. I believe that the field of communication studies should do more work in agriculture, because it would improve the relationship between these two fields and enhance research in both fields as well. There is little communication studies scholarship in the field of agriculture and education, and my hopes with this research is to bridge these two fields.
Keywords: Communication studies; Intersectionality; Agricultural feminism; Organizational communication; Student perspectives